Development of a set of monosomic alien addition lines from Gossypium raimondii in Gossypium hirsutum toward breeding applications in cotton - Zhenzhen Xu; Xiaoxi Lu; Wenjie Ding; Wei Ji; Wuzhimu Ali; Heyang Wang; Shan Meng; Qi Guo; Peng Xu; Xianglong Chen; Liang Zhao; Huan Yu; et al. (BMC Plant Biology)
Abstract Background Gossypium raimondii Ulbr is a diploid wild cotton (2n = 26, D5D5) that originated in west-central Peru of South America and possesses desirable characteristics that are absent in the Upland cotton G. hirsutum. Many beneficial genes were lost from G. hirsutum in the process of domestication, leading to a narrowed genetic base and greater vulnerability to biotic and abiotic stresses. This genetic base can be expanded through distant hybridization using the superior genes of G. raimondii. Results In this study, putative hexaploid F1 plants of G. hirsutum - G. raimondii were generated by interspecific hybridization. Analysis of its mitotic metaphase plates revealed the presence of 78 chromosomes, with each of the six chromosome-specific fluorescence in situ hybridization (FISH) probes (3D5, 5D5, 6D5, 7D5, 9D5, and 10D5) of G. raimondii exhibiting bright and distinct signals on its respective pair of chromosomes. Then, the fertile hexaploid F1 plants were continuously backcrossed with G. hirsutum and a set of G. hirsutum - G. raimondii monosomic alien addition lines (MAALs) were developed using SSR markers in successive backcrosses and self-crossing from BC2F1 to BC4F2. These MAALs were confirmed by chromosome-specific anchored SSRs and FISH. This set of MAALs exhibited abundant variation in morphological traits, agronomic characteristics, yield, and fiber quality traits, as well as in drought and salt resistance at seedling stage. Notably, MAAL_9D5 and MAAL_10D5 demonstrated excellent fiber length (FL), fiber uniformity (FU), fiber strength (FS), micronaire value, and fiber elongation (FE); At seeding stage, MAAL_8D5, MAAL9D5, MAAL_10D5, MAAL_12D5, and MAAL_13D5 showed salt resistance potential; while MAAL_1D5, MAAL_3D5, MAAL_4D5, MAAL_7D5, MAAL_8D5, MAAL_12D5, and MAAL_13D5 exhibited drought resistance potential. These MAALs will provide important genetic bridge materials for gene transfer from G. raimondii as well as for the study of Gossypium species genomes and their evolution. Conclusions A set of Gossypium hirsutum - Gossypium raimondii MAALs were developed and they showed abundant variation in morphological, agronomic, yield, and fiber quality traits, as well as in drought and salt resistance at seedling stage.